Motivation And Physical Activity: Correlation Study on Extracurricular Sports of High School Students - Oktadinata, Alek; Prabowo, Bangkit Yudo; Daya, Wawan Junresti; Diana, Fitri; Nugraha, Ugi; Melinda, Melinda; Ockta, Yovhandra (STKIP Singkawang, 2024)
Problems arise when students feel less enthusiastic about extracurricular sports activities. This is an indication of the quality of physical activity. This research is a correlational research aimed at finding out whether there is a relationship between motivation and physical activity of students who take part in extracurricular sports at State High School 8 Merangin. This research method uses a quantitative descriptive method. The population in this study was class X extracurricular sports students at State High School 8 Merangin, totaling 118 students. Determining the sample in this study used a simple random sampling technique using the Slovin formula to obtain a sample of 33 students. Data collection used a motivation questionnaire and the international physical activity questionnaire (IPAQ). Based on the results of the data, the overall relationship between motivation and physical activity has a correlation coefficient value of (0.391) in the strong category, the relationship between intrinsic motivation and physical activity has a correlation coefficient value of (0.407) in the strong category and the relationship between extrinsic motivation and physical activity has a correlation coefficient value of (0.135). in the weak category. The conclusion illustrates that there is a positive relationship between motivation and extracurricular sports activities of students at State High School 8 Merangin in the strong category.